Characteristics Of Early Childhood Cognitive Development Through Learning Islamic Religious Education In Early Childhood Education - Hidayat, Arif (Naturalistic: Jurnal Kajian dan Penelitian Pendidikan dan Pembelajaran, 2025)
Islamic Religious Education (IRE) at the Early Childhood Education (ECE) level faces challenges in applying approaches that are in accordance with the characteristics of children's cognitive development. There is still a tendency to use verbalistic and abstract methods that are not in accordance with the concrete needs of children, so that the process of internalizing religious values is less than optimal. This research aims to examine how IRE learning can contribute to early childhood cognitive development. The main focus is to identify the characteristics of cognitive development that arise through contextual learning approaches, experience-based, and oriented to the internalization of religious values. The research method used is qualitative literature, which involves problem identification, source tracking, critical analysis and synthesis of findings to build a comprehensive understanding. The findings show that through a concrete experience-based learning approach, children can understand religious concepts in a simpler and more meaningful way. In addition, the internalization of religious values adapted to the stage of cognitive development of children can strengthen the foundation of critical thinking, morals, and spirituality. This research provides important pedagogical implications in designing learning that is responsive to children's developmental needs, as well as enriching the theory and practice of Islamic religious education in ECE.